E-SULAM Preservation of Bidayuh Language and Culture - Yvonne Michelle, Campbell (UNIMAS Publisher, 2023)
This project was originally a SULAM (Service Learning Malaysia - University for Society) project, however due to the COVID-19 pandemic and MCO, it was modified into an eSULAM project. The main outcome at the end of the day was that the students can come up with a way to preserve, sustain and disseminate knowledge of language and culture of a chosen community, which in this case is the Bidayuh community. The product decided after much discussion amongst the students was a website to showcase information about the Bidayuh language and culture.